Hemiodus iratapuru, a new species of Hemiodontidae from the Rio Jari, Amazon Basin, Brazil (Teleostei, Characiformes) - Langeani, F. [UNESP]; Moreira, C. R. (Wiley, 2013)
Hemiodus iratapuru, a new species of the Hemiodontidae from the Rio Iratapuru, a left bank tributary of the Rio Jari, Amazon Basin, Brazil, is described. The new species is diagnosed from other species of Hemiodus by modifications in the ectopterygoid, tooth form, scale counts, dorsal-fin form and colour pattern. The new species is proposed to be related to the Hemiodus quadrimaculatus species group. © 2013 The Authors. Journal of Fish Biology © 2013 The Fisheries Society of the British Isles.
Keywords: Amapá; Guyana shield; Hemiodus quadrimaculatus; Pará; animal; Brazil; Characiformes; classification; histology; river; Animals; Rivers; Hemiodontidae; Hemiodus; Teleostei